Polydopamine-Based Surface Modification of ZnO Nanoparticles on Sericin/Polyvinyl Alcohol Composite Film for Antibacterial Application - Lisha Ai; Yejing Wang; Gang Tao; Ping Zhao; Ahmad Umar; Peng Wang; Huawei He (Molecules, 2019)
Silk sericin (SS) is a type of natural macromolecular protein with excellent hydrophilicity, biocompatibility and biodegradability, but also has very poor mechanical properties. To develop sericin-based wound dressings, we utilized polyvinyl alcohol (PVA) to reinforce the mechanical property of sericin by blending PVA and sericin, then modified zinc oxide nanoparticles (ZnO NPs) on SS/PVA film with the assistance of polydopamine (PDA) to endow SS/PVA film with antibacterial activity. Scanning electron microscopy, energy dispersive spectroscopy and X-ray powder diffraction demonstrated ZnO NPs were well grafted on PDA-SS/PVA film. Fourier transform infrared spectra suggested PDA coating and ZnONPs modification did not alter the structure of sericin and PVA. Water contact angle and swelling tests indicated the excellent hydrophilicity and swellability of ZnO NPs-PDA-SS/PVA composite film. Mass loss analysis showed ZnO NPs-PDA-SS/PVA film had excellent stability. The mechanical performance test suggested the improved tensile strength and elongation at break could meet the requirement of ZnO NPs-PDA-SS/PVA film in biomaterial applications. The antibacterial assay suggested the prepared ZnO NPs-PDA-SS/PVA composite film had a degree of antimicrobial activity against Escherichia coli and Staphylococcus aureus. The excellent hydrophilicity, swellability, stability, mechanical property and antibacterial activity greatly promote the possibility of ZnO NPs-PDA-SS/PVA composite film in antibacterial biomaterials application.